The Influence of Human Resource Development on Employee Performance in the Business Support Section of PT Sucofindo Medan Branch - Rivanka, Weny; Aslami, Nuri (Universitas Ibn Khaldun, 2024)
In life in the world of work, there must be things that are contrary to the performance of employees in their work. Of course, there is still something strange when working that immediately does not support the values of a job, with human resources having a very important role and needs to be given serious attention. Employees or employees as human resources are very vital in improving the performance or even progress of an organization. This research was conducted to determine the extent of the influence of human resource development on employee performance in the business support section of PT Sucofindo Medan Branch. The results of research conducted in the business support section of PT Sucofindo Medan Branch where with the interview method to the office employees, the researcher got a result, which turned out by all means and development of human resources in this office such as training, evaluating and improving performance made human resources in this office better. By using qualitative methods through interview techniques with employees in the business support section of PT Sucofindo Medan Branch, it is expected that the data received will be reliable and have good value. In addition, researchers also improve by looking for several references from previous studies so that the results made will be even better content.